Clastogenicity of Piper cubeba (Piperaceae) seed extract in an in vivo mammalian cell system - Junqueira, Adriana Pereira Freire [UNESP]; Perazzo, Fabio Ferreira; Souza, Gustavo Henrique Bianco; Maistro, Edson Luis [UNESP] (Sociedade Brasileira de Genética, 2007)
The plant Piper cubeba is widely distributed in tropical and subtropical regions and is used medically for various purposes but has not yet been evaluated for genotoxicity. We used male and female Swiss mice and Wistar rats and the comet assay and micronucleus test to investigate the mutagenic potential of a crude extract of P. cubeba seeds. The rodents were administered 0.5 g kg-1, 1.0 g kg-1 and 1.5 g kg-1 of the extract by gavage. For the Swiss mice, peripheral blood was collected 24 h after treatment for the comet assay, and at 48 and 72 h for the micronucleus test. For the Wistar rats, peripheral blood and hepatic cells were collected for the comet assay and bone marrow cells were collected for the micronucleus test 24 h after treatment. At 1.5 g kg-1, the highest dose tested, the extract induced a statistically significant increase in both the mean number of micronucleated polychromatic erythrocytes and the level of DNA damage in the rodent cell types analyzed. Under our experimental conditions, the P. cubeba seed extract was genotoxic in vivo when administered orally to mice and rats.
Keywords: micronucleus test; Piper cubeba; single cell gel electrophoresis (SCGE)